Pemanfaatan Lidi Menjadi Kerajinan Ingke Dalam Peningkatan Perekonomian Usaha Mikro di Desa Gegelang, Karangasem - Ida Ayu Surasmi; I Gusti Ayu Intan Saputra Rini; I Made Jamin Yasa (Universitas Warmadewa, 2023)
Gegelang Village is one of the villages in Manggis sub-district, Karangasem district. There are 6 banjars in Gegelang, namely Telengan, Karanganyar, Gegelang, Pakel, Babakan and Panggung. This village has the potential for natural products, namely coconut trees. Coconut has many benefits, one of which is that the stems of coconut leaves can be used to make woven craft products, namely ingke. In Bali, Ingke is used as a place for offerings in prayer. Not only as a place for offerings or offerings, ingke is also used as a dinner plate which is usually topped with banana leaves or oil paper. An interesting phenomenon in ingke crafts is the current trend of using ingke as a substitute for offering containers or as a substitute for plates and other containers because it is considered very efficient and effective. However, the phenomenon that occurs among craftsmen in Andakasa is actually decreasing. This is due to problems including limited sticks being sold in the market area, sales are adjusted to orders, the number of orders cannot be fulfilled when there is a shortage of raw materials, the raw materials produced do not have a pattern, the value or price of the product. the input is process-based. bargaining and the absence of standard standards, increasingly complex market conditions and competition in trade. Therefore, the community service team can participate together to help increase the number of sales of ingke production, so that it can improve the economy, especially Banjar Pakel in Gegelang Village.